Photogyrotactic Concentration of a Population of Swimming Microalgae Across a Porous Layer - Prakash, Praneet; Croze, Ottavio A. (Frontiers in Physics, 2021)
The light environment controls the swimming of microalgae through a light-seeking and avoiding behaviour, which is known as phototaxis. In this work, we exploit phototaxis to control the migration and concentration of populations of the soil microalga Chlamydomonas reinhardtii. By imaging a suspension of these microalgae in a cuvette illuminated from above by blue light, we study how phototaxis changes the stability of the suspension and demonstrate how a thin, porous layer at the top of the cuvette prevents phototaxing microalgae from sinking, leading to the up-concentration of the microalgae in the region above the porous layer. We discuss the potential implications of our findings for microalgae in biotechnological applications and the natural environment.